Concentrações de fósforo e nitrogênio no crescimento da alface em cultivo sem solo - Silva, Juliete Araújo da (2018)
The goal of this research was to evaluate phosphorus and nitrogen concentrations on growth and in soilless lettuce plants. Experiments were carried out inside a polyethylene greenhouse at Plant Science Department at the Santa Maria Federal University (UFSM) from 2015 to 2017. In the first step, four experiments were conducted in spring 2015, autumn 2016, summer 2017 and winter 2017, to determine the effect of low and high P concentrations in the nutrient solution on growth and commercial production of lettuce plants. In experiments spring and autumn treatments were high P concentrations (1.5; 3.0; 4.5 e 6.0 mmol L-1) and two cultivars Stella and Veneranda. In experiments summer and winter, five low concentrations were (0.4; 0.8; 1.2; 1.6 e 2.0 mmol L-1) and two cultivars (Stella and Veneranda). The second stage consisted of two experiments conducted inside a polyethylene greenhouse in 2017. At the shelter N and P concentrations, respectively, high (NHPH), high and low (NHPL), low and high (NLPH), low (NLPL) and control defined as the better concentration from previous experiments and two lettuce cultivars (Stella and Veneranda) at two growing seasons (autumn and autumn-winter). In all experiments, a factorial experimental randomized experimental design was used, with seasons, concentrations and cultivars. Results showed that P concentrations in nutrient solution above and below 2.1 mmol L-1 in spring/summer and 2.37 mmol L-1 in autumn/winter reduce lettuce growth in soilless culture, with stronger effect on concentrations above these values. Antagonistic interactions between N and P concentrations in the nutrient solution were not observed in roots and shoot. Maximum shoot growth and P accumulation in tissues is reached at 2.1 mmol L-1 P concentration in the nutrient solution. There are any interactions between P and N in the nutrient solution with reduction in accumulation of other nutrients.